Occurrence, spatial distribution, potential sources, and risk assessment of common antibiotics in surface seawater of the Northeastern Indian Ocean - Jiuming Wang; Ruixue Hao; Yuanxin Cao; Xiuping He; Fengjun Wang; Haiyuan Wang; Junhui Chen (Environmental Research Letters, 2025)
The increasing entry of antibiotics into the marine environment has led to marine pollution and the potential global spread of antibiotic resistance genes, posing a threat to both marine ecosystems and human health. Compared with β -lactam and sulfonamide antibiotics, tetracycline and quinolone antibiotics have longer environmental half-lives and are more widely used, particularly in agriculture, aquaculture, and healthcare. In this study, the composition, spatial distribution, potential sources, and ecological risks of 4 tetracycline and 20 quinolone antibiotics were systematically investigated by liquid chromatography tandem mass spectrometry (LC-MS/MS) in the surface seawater of the Northeastern Indian Ocean for the first time. A total of nine antibiotics were detected in seawater samples, including tetracycline (detection rate: 100%), oxytetracycline (100%), chlortetracycline (100%), doxycycline (100%), ofloxacin (100%), ciprofloxacin (100%), norfloxacin (92.3%), enrofloxacin (96.2%), and fleroxacin (23.1%). Tetracycline, oxytetracycline, chlortetracycline, doxycycline, ofloxacin, ciprofloxacin, norfloxacin, and enrofloxacin were widely distributed throughout the study area, with tetracycline antibiotics (83.8%) being significantly more prevalent than quinolone antibiotics. Among them, oxytetracycline was the dominant tetracycline antibiotic. The concentrations of tetracycline and quinolone antibiotics ranged from 0.258 to 23.521 ng l ^−1 (mean: 16.813 ng l ^−1 ) and 0.016–9.480 ng l ^−1 (mean: 3.261 ng l ^−1 ), respectively. The highest concentrations were found in the northeastern region of the study area. Aquaculture and livestock farming in Myanmar, Thailand, and Malaysia were identified as potential sources of these antibiotics. Ecological risk assessments indicated that ciprofloxacin poses a moderate risk to aquatic organisms in the Northeastern Indian Ocean. This study provides new insights into antibiotic pollution in the open waters of the Indian Ocean and highlights the urgent need for further research on the ecological impacts of these emerging pollutants in marine environments.